Changes in Th9 and Th17 lymphocytes and functional cytokines and their relationship with thyroid-stimulating hormone receptor antibodies at different stages of graves’ disease - Ren, Xuan; Chen, Hui (Frontiers in Immunology, 2022)
Objective: Graves' disease (GD) is an organ-specific autoimmune disease characterized by the production of thyroid-stimulating antibodies (TSAb). The newly discovered CD4+ T helper cells, Th9 and Th17 lymphocytes, have been confirmed to be closely associated with a variety of immune diseases. However, relationships with the onset and development of GD remain unclear. The purpose of this study was to investigate the roles of Th9 and Th17 in the pathogenesis and prognosis of GD. Design: Patients: We recruited 26 patients with newly diagnosed GD, 45 patients with GD in remission, and 20 healthy individuals. Measurements: Thyroid function and autoantibodies were evaluated using chemiluminescence immunoassays. Th9 and Th17 cells were analyzed using flow cytometry. The expression of Foxo1, IRF-4, RORc, IL-9, and IL-17 mRNA was examined using real-time PCR, and IL-9 and IL-17 protein levels were measured using enzyme-linked immunosorbent assay. Results: Th9, Th17, and characteristic cytokines IL-9 and IL-17 in the GD-untreated group were significantly higher than those in the control and remission groups. The above indexes significantly decreased in the remission group, with the levels in the TRAb− remission group being similar to those in the normal group, while in the TRAb+ remission group, levels were differentially increased. TRAb titer was positively correlated with the levels of Th9, Th17, and their functional cytokines. Conclusions: Th9 and Th17 cells may be involved in the pathogenesis and disease outcome of GD, which could provide a new direction for developing immunotherapy for patients with GD.